(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This study presents an experimental investigation into the wave-induced motion of a 31 mm diameter power cable model, with a mass ratio of 2.08, configured in a lazy wave arrangement—a typical configuration for offshore applications. The experiment explores the dynamic response of the cable model under varying wave directions. The cable was tested under regular waves and combined wave-current conditions, where currents were aligned in three orientations: following and perpendicular to the wave direction, at incident angles of 0°, 90°, and 180° relative to the cable axis. Bending strains were measured at seven locations along the cable using strain gauges. The variations in bending strain at each location were analyzed. Under wave-only conditions, the cable’s peak frequencies corresponded to the wave frequency and its harmonics. However, in the presence of currents, additional frequency components were observed, indicating the influence of vortex-induced vibrations (VIV). Higher current magnitudes amplified these effects, altering the frequency response and increasing the secondary peak intensities. These findings underscore the complex interaction between waves and currents on power cables, highlighting the critical role of wave direction, current magnitude, and combined hydrodynamic forces in influencing cable dynamics. The results have practical implications for offshore power cable design and reliability in dynamic marine environments.